Effectiveness of using technology based songs to enhance vocabulary competency among year two undergraduate students at Universiti Malaysia Sabah (UMS) - Tracy Joann Stanlee; Soon Singh A/L Bikar Singh (USIM PRESS, 2021)
The general standard of English among Malaysian students is poor considering that they receive 11 to 13 years of formal English lessons at both primary and secondary level. As a result, they often need to re-take the Malaysian University English Test (MUET) in order to fulfill the English proficiency requirements for university entry. The unsatisfactory level of students’ English has attracted the attention of educators, becoming a topic of concern for the government and local communities. Advances in technology that have signaled Industrial Revolution 4.0, prompted the researchers to explore the effectiveness of employing technology-based songs to enhance vocabulary competency among students taking English subjects. A total of 65 students took part in a seven-week research study based on a quasi – experimental design. From the sample, 35 students were placed in the experimental group and taught English vocabulary via music videos as a form of intervention. The remaining 30 students were placed in a control group and taught via traditional methods. Pre and post-tests involving vocabulary questions were distributed to all 65 students. Paired Sample T–Tests were then conducted and analyzed: the findings indicated that the mean score for the experimental group was statistically higher than that for the control group. This research may help educators to gain more ideas about employing technology to deliver teaching more effectively; and has indirectly demonstrated more effective procedures for enhancing 21st Century skills which align with the aims of Industrial Revolution 4.0.